Transmission SystemLoadability Improvement using FACTs - Mohammed, Mariya; Abdallah, Mohammed Ali (International Journal of Psychosocial Rehabilitation, 2020)
Due to the increasing demand for electricity and transactions in power markets, existing power grids need to be enhanced in order to increase their loadability.Flexible AC Transmission Systems (FACTS) technology is very beneficial in enhancing power flow along transmission lines and making the power grid more efficient and controllable. In this paper two types of FACTS devices, STATCOM and TCSC, placed on buses and transmission lines. Many cases studywere taken to test how the system acts in the presence and absence STATCOM or/and TCSC under increase load and outage line conditions. Both STATCOM and TCSC in same zone work to reduce the over load line, improve the bus voltage, and return the system to its working limits after contingency conditions. STATCOM or/and TCSC steady-state model was adopted on the IEEE-30 bus test system and tested using the MATLAB programming language. Newton-Raphson numerical analysis approach was used to solveSTATCOM or/and TCSC load flow.